Third-order Nonlinear Optical Response and Ultrafast Carrier Dynanics of 2D Materials - WANG, GAOZHONG (Trinity College Dublin. School of Physics. Discipline of Physics, 2018)
Two dimensional (2D) materials have been in the spotlight of scientific researchers in the last decade due to their outstanding chemical, physical, electronic, mechanical and optical properties in comparison to their bulk. Strong photoluminescence was observed in 2D materials because of the transition from indirect bandgap semiconductor in bulk limit to direct bandgap in monolayer limit. 2D materials have also attracted tremendous interest due to their quantum confinement which results in intriguing physical phenomenon at room temperature, such as optical Stark effect, stable exciton, trion formation and exciton-exciton annihilation etc. These make them promising candidates for applications in the field of spintronics, valleytronics, optoelectronics and nano-electronics. However, the optical and physical performance of many 2D materials are still under questions and their excited carrier dynamics remains unclear. Therefore it is interesting and necessary to study their nonlinear optical performance and ultrafast carrier dynamics relative to the above mentioned field. In this thesis, the nonlinear optical behaviors and ultrafast exaction carrier dynamics of several 2D materials, including graphene saturable absorption mirror (GSAM), layered antimony, platinum diselenide, transition metal dichalcogenides (TMDs, e.g., tungsten disulfide, molybdenum disulfide and molybdenum diselenide), and their polymer composites (e.g. molybdenum diselenide/PVA composites), were investigated from visible to infrared range. The GSAM was fabricated through a vacuum-filtrated transfer of liquid-phase-exfoliated graphene onto a silver-coated mirror. Liquid-phase-exfoliation technique was also employed to prepare layered TDMs. Meanwhile, Chemical vapor deposition (CVD) method was utilized to fabricate layered platinum diselenide by direct selenization of previously deposited Pt atom layer on substrate. The layer structure and high quality of these 2D materials was verified by scan electron microscopy (SEM), transmission electron microscopy (TEM), atomic force microscopy (AFM) and Raman spectrum. In terms of optics, nonlinear optical response of the above 2D materials were systematically studied by spatial self-phase modulation (SSPM), Z-scan and I-scan, while their ultrafast excitation carrier dynamics was characterized by time-resolved degenerate femtosecond pump-probe technique and spectra-resolved transient absorption spectroscopy. Firstly, SSPM technique based on continuous wavelength lasers in the visible range was utilized to study the coherent nonlinear optical behaviors of the above TMDs and layered antimony. From SSPM experiments, one is able to calculate the nonlinear refractive index and third-order nonlinear optical susceptibility, which are two of the important parameters in nonlinear optics. By changing the incident laser intensity to tune the distortion of SSPM pattern, the relative effective nonlinear refractive index can be modulated. Secondly, saturable absorption behavior, one of most important nonlinear response, was observed in layered antimony, platinum diselenide and molybdenum diselenide/PVA composites using the Z-scan technique. By applying a typical nonlinear theory and slow-absorber model to analyze the Z-scan data in the visible regime, the key nonlinear parameters such as nonlinear absorption coefficients were extracted. Thirdly, the photonic performance of a graphene saturable absorption mirror (GSAM) based on liquid-phase-exfoliation at mid-infrared regime was compared with a commercial semiconductor saturable absorption mirror (SESAM, BATOP, SAM-2000-44-10ps) using a reflective I-scan method. The linear reflection of the GSAM was designed to be similar to that of the commercial SESAM (~64%). A reflective slow-absorber mirror model modified from slow-absorber theory was applied to analyze I-scan data and the results show that the GSAM has a comparable non-saturable loss 9.9% and modulation depth of ~13%. By subtracting the 13.8% surface scattering of GSAM, the theory calculation indicated that GSAM have better nonlinear optical performance than the commercial SESAM. The cross-section ratio of excited-state over ground state is fitted to be 0.442 and 0.615 for graphene and SESAM respectively, implying graphene based SAM would have less loss and heat than SEAM in a laser cavity. Finally, transient absorptive mapping and degenerate femtosecond pump-probe results signify that layered platinum diselenide crystals exhibit broadband excited-stated absorption and the excited carriers exhibited three decays. By employing a three-dimensional (3D) triexponential and biexponential decay models to fit the differential transmission traces, the carrier life times of layered platinum diselenide crystalline were figured out. The first fast decay process was attributed to carrier-carrier scattering while the second fast relaxation was dominated by intraband carrier-phonon and carrier-carrier scattering. The slowest relaxation is attributable to the indirect recombination of electron-hole pairs. These results offer systemic insights into photophysical properties like nonlinear optical response and ultrafast excitation carrier dynamics of 2D materials in question, with their applications for photonic, photovoltaic, optoelectronic and nano-electronic devices.
APPROVED
Keywords: 2D Materials, Layered Platinum Diselenide, Polymer Composites, Nonlinear Optics, SSPM, Saturable Absorption, Z-scan, Slow-absorber, Mode-locker, I-scan, GSAM, SESAM, Carrier Dynamics, Pump-probe, Transient Absorption Spectroscopy